Advances in nanotechnology and the environment - Kim, Juyoung (Singapore : Pan Stanford, 2012)
'Nanoparticles and nano-sized materials created by nanotechnology (NT) have been considered unique and sole solution to overcome the limitations of other technologies and widen their applications. Although these materials have been widely used in environmental technology (ET), most of environmental applications of nanoparticles were limited to the fabrication of nano-sensors for the detection of volatile organic compounds (VOC) and as nano-sized catalysts for air purification systems. So, the use of nanoparticles for the direct removal of pollutants from contaminated soil and wastewater has been seldom reported. However, environmental processes for soil remediation, wastewater treatment, and air purification strongly need innovative new materials to highly improve their performance and efficiency. So, demands for materials created by NT in ET are stronger than ever.
This book presents the possible applications of nano-sized materials in all environmental processes, providing the most reliable guideline for the selection of nanomaterials to improve the efficiency of environmental processes. It focuses on designing specific nanomaterials for environmental processes and pollutants. It presents the impact and influence of nanomaterials on the environment and discusses how to avoid causing secondary contamination by the use of nanomaterials. The book provides proper information about nanomaterials for potential users who will use and apply nanomaterials in ET.'--Publisher's description.
Includes bibliographical references and index.
Keywords: Nanotechnology -- Environmental aspects; Environmental engineering